Gender Differences in Online Mass Customization: An Empirical Consumer Study Which Considers Gift-Giving - Walcher, Dominik; Leube, Michael; Blazek, Paul (International Journal of Industrial Engineering and Management, 2016)
Although several studies on gender commerce were published in the last decade, showing the importance of a differentiated address of men and women in marketing, studies on gender differences in online mass customization (MC) are rare. With the help of an empirical study it was analyzed which categories of customized products are preferred by women and men and if products are bought for self-usage or for gift-giving. A quantitative study with 247 participants showed that products in the categories “food & nutrition” as well as “personalized look” are preferably bought by women, whereasproducts in the categories“ made-to-measure-apparel” and “footwear” are predominantly purchased by men. The research showed that, in all product categories considered, women customized products for gift-giving more than men. This result follows the theoretical foundation in evolutionary psychology. In addition, in the category “personalized fashion” women bought significantly more products (i.e. printed T-shirts) to give as a gift to others than men. Based on the results of the study recommendations for adapting the customization process to the gender of the users and the objective of purchase are given. Article history: Received (02.11.2016); Revised (23.11.2016); Accepted (19.12.2016)